The herpetological importance of Mt. Hamiguitan Range, Mindanao Island, Philippines - Delima, Elsa May M. (Banwa, 2007)
We provide the first accounts of the amphibians and reptiles of Mt. Hamiguitan Range in south eastern Mindanao. Three sites were visited: dipterocarp, transitional dipterocarp-montane and mossy-pygmy forests. The combination of transect sampling, pitfall trapping and microhabitat searches produced records of 34 species (15 frogs, 14 lizards and five snakes). We provide information on the herpetofaunal assemblage of Mt. Hamiguitan including data on species richness, elevational distribution and microhabitat preferences. High levels of species richness and endemism were observed especially in the dipterocarp forest site located outside the boundaries of the protected area. Our data suggest that Mt. Hamiguitan range should be considered an important subcenter of herpetological diversity. Future conservation efforts should focus particularly on lowland forests.